PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. IKHTIAR RIAU JAYA RAYA PERANAP - Sinaga, Rodiuta Tuditado; Andri, Seno (Jurnal Daya Saing, 2024)
This research aims to analyze the influence of transformational leadership style (X1), Work Discipline (X2), on Employee Performance (Y) at PT. Riau Jaya Raya's endeavor. This research uses quantitative methods by distributing questionnaires to 32 employees. The data analysis technique used is multiple linear regression analysis using SPSS version 25. Based on the results of the partial analysis, Transformational Leadership Style has a positive effect on Employee Performance, this is because the t-count obtained is greater than the t-table value (3.006>1.310). Work Discipline has a positive effect on Employee Performance, this is because the t-count obtained is greater than the t-table (4.509>1.310). Meanwhile, the F test shows that there is a simultaneous relationship between variables X and Y because the F-calculated value is greater than the F-table (12,600>3.33). Keywords: Transformational Leadership Style, Work Discipline, Employee Performance